CRIANÇAS CINEASTAS E SEUS ROTEIROS CRIARTEIROS: INFÂNCIAS, CURRÍCULOS E DOCÊNCIAS INVENTIVAS - Zouain, Ana Claudia Santiago (2019)
This dissertation goes through the thought movements of children and teachers in the encounter with cinema and school images. It deals with inventive cartographies in the school daily life of a Federal Center of Early Childhood Education in the city of Vi